N-Hydroxyimides and hydroxypyrimidinones as inhibitors of the DNA repair complex ERCC1–XPF. Issue 19 (1st October 2015) - Chapman, Timothy M.; Wallace, Claire; Gillen, Kevin J.; Bakrania, Preeti; Khurana, Puneet; Coombs, Peter J.; Fox, Simon; Bureau, Emilie A.; Brownlees, Janet; Melton, David W.; Saxty, Barbara
Graphical abstract: Abstract: A high throughput screen allowed the identification of N -hydroxyimide inhibitors of ERCC1–XPF endonuclease activity with micromolar potency, but they showed undesirable selectivity profiles against FEN-1. A scaffold hop to a hydroxypyrimidinone template gave compounds with similar potency but allowed selectivity to be switched in favour of ERCC1–XPF over FEN-1. Further exploration of the structure–activity relationships around this chemotype gave sub-micromolar inhibitors with >10-fold selectivity for ERCC1–XPF over FEN-1.